Maternal zinc serum levels and association with pre-eclampsia - A systematic review (Research, Society and Development, 2021)
Objective: To carry out a study to compile evidence on the association between the serum levels of maternal Zn and the occurrence of preeclampsia in pregnant women. Methodology: This is a systematic review of the literature, the search for scientific articles was carried out by the authors independently, between May and June 2021, in the following electronic databases: National Library of Medicine (PubMed), Scopus and Science Direct. Using as controlled descriptors identified in the Descriptors of Health Sciences (DECs) the following combination in English: (“Zinc AND pre-eclampsia”). After the article search strategy, the titles were read, after the summaries and, finally, the full text to build the results table. Results: A total of 1088 articles were found through the search in the databases, after the screening process, it resulted in a total of 11 articles chosen for measuring the results, these were case-control studies, comparative cross-sectional study, cross-sectional analytical study and prospective cohort, published from 2016 to 2021, being carried out with women with PE and normotensive, aged over 17 years. Conclusion: The majority of the studies found a relationship between the low levels of zinc and the preeclampsia, understanding that there is a correlation between them, but the studies are contradictory, and that some authors have not found this association. Without embargo, it is necessary to carry out more accurate studies on the subject for a better understanding.